PERAN GURU DALAM MENGEMBANGKAN KECERDASAN MUSIKAL ANAK USIA DINI MELALUI KEGIATAN EKSTRAKURIKULER DRUMBAND DI TK MUSLIMAT NU 001 PONOROGO - Mahmudah, Amin; Rohmah, Umi (Institut Agama Islam Negeri Ponorogo, 2020)
Abstract: Musical intelligence of a child's ability to store notes, remember rhythm and be emotionally affected by music. The development of musical intelligence is one of them by the drumband extracurricular activities. This study aims to: (1). know the role of the teacher as a facilitator in developing early childhood musical intelligence through Drumband Extracurricular activities at Muslimat Nu 001 Ponorogo Kindergarten. (2). know the role of the teacher as a guide in developing musical intelligence of Early Childhood through Drumband Extracurricular activities at Muslimat Nu 001 Ponorogo Kindergarten. This research uses a qualitative approach with case study research. The technique used in collecting data is to use observation, interview, and documentation techniques. While the data analysis technique used is to use the Milles Hiberman technique. The results of this study are (1) the teacher's role as a facilitator is as a provider of the tools needed during the exercise and checking the condition of the tools. (2) the teacher's role as a guide in is to provide guidance and train children in the technique of punching in accordance with the tempo, training and accustoming children to discipline in drum exercises.